Roles of Ce1−xZrxO2/SBA‑15 in Selective Catalytic Glycerol Conversion to Lactic Acid Process : Process Behaviors and Kinetic Analyses - Syamima Nasrin, Mohamed Saleh; Fakhrony Sholahudin, Rohman; Anwar, Ul-Hamid; Ahmad Zuhairi, Abdullah (Springer Nature, 2024)
The surge in glycerol production from the oleochemical industry prompted the aggressive search for new value-added derivatives such as lactic acid. A series of novel Ce1− xZrxO2 catalysts on mesoporous SBA-15 were synthesized and tested in a 50 mL reactor for up to 2 h for oxidative lactic acid synthesis from glycerol. A suitable kinetic model to represent the reaction was identified and kinetic parameters were calculated. The 10Ce1−xZrxO2/SBA-15 catalyst, at a 15 wt% catalyst-toglycerol ratio, exhibited impressive activity, achieving 94.2% glycerol conversion and 45.3% lactic acid yield at 260 °C. The reaction model shows good agreement with experimental data across various reaction conditions (R2 values between 0.90 and 1.00). Based on a pseudo-second-order kinetic model, the selective conversion of glycerol to lactic acid was found to have an activation energy of 165.3 kJ/mol, with a high R2 value of 0.94 which was lower than some reported results.